Tumor Derived SIGLEC Family Genes May Play Roles in Tumor Genesis, Progression, and Immune Microenvironment Regulation - Chen, Zheng; Yu, Mincheng; Guo, Lei; Zhang, Bo; Liu, Shuang; Zhang, Wentao; Zhou, Binghai; Yan, Jiuliang; Ma, Qianni; Yang, Zhangfu; Xiao, Yongsheng; Xu, Yongfeng; et al. (Frontiers in Oncology, 2020)
Background SIGLEC family genes can also be expressed on tumor cells in different cancer types, and though it has been found SIGLEC genes expressed by immune cells can be exploited by tumor to escape immune surveillance, functions of tumor derived SIGLEC expression in tumor microenvironment (TME) were barely investigated, which could play roles in cancer patients’ survival. Methods Using bioinformatic analysis, mutation status of SIGLEC family genes were explored through cBioPortal database, and expression of them in different tumors were explored thorough UALCAN database. GEPIA database was used to compare SIGLEC family genes’ mRNA between cancers and to generate a highly correlated gene list in tumor. KM-plotter database was used to find the association between SIGLEC genes and survival of patients. The associations between SIGLEC family genes’ expression, immune infiltration and immune regulators’ expression in TME were generated and examined by TIMER 2.0 database; the differential fold changes of SIGLEC family genes in specific oncogenic mutation groups of different cancer types were also yielded by TIMER 2.0. The networks of SIGLEC family genes and highly correlated genes were constructed by STRING database, and gene ontology and pathway annotation of SIGLEC family highly correlated genes were performed through DAVID database. Results SIGLEC family genes were highly mutated and amplified in melanoma, endometrial carcinoma, non-small cell lung cancer, bladder urothelial carcinoma and esophagogastric adenocarcinoma, while deep deletion of SIGLEC family genes were common in diffuse glioma. Alteration of SIGLEC family genes demonstrated different levels in specific tumors, and oncogenic mutation in different cancer types could influence SIGLEC family genes’ expression. Most SIGLEC family genes were related to patients’ overall survival and progression free survival. Also, tumor derived SIGLEC family genes were related to tumor immune cell infiltration, and may regulate TME by influencing chemokine axis. Conclusion Our computational analysis showed SIGLEC family genes expressed by tumor cells were associated with tumor behaviors, and they may also influence TME through chemokine axis, playing vital roles in patients’ survival. Further experiments targeting tumor derived SIGLEC family genes were needed to confirm their influences on tumor growth, metastasis and immune environment regulation.